Potensi Energi Listrik Pada Gas Buang Sepeda Motor - Melda Latif; Nuri Hayati; Uyung Gatot S Dinata (Jurnal Rekayasa Elektrika, 2015)
The fossil energy sources dwindling due to the many needs, especially in industrial and automotive sectors which are the largest energy users and the highest waste heat-producing. This causes many alternative energy sources are developing, included thermal energy utilization. The research utilized waste heat energy from motorcycle exhaust pipe into electrical energy with using Thermo Electric Generator (TEG). By using the thermocouple principle, difference of temperature between hot and cold side of TEG resulted voltage. Testing was conducted with three points are on head, body and mouth of the exhaust pipe. The maximum output voltage is generated in the head is greater than the other positions. At the head of exhaust, the maximum output voltage which is generated by 1 modul, 2 modules and 3 modules of TEG on each other is 1.26 V, 2.27 V and 3.43 V respectively.